Monitoring training load and fatigue in rugby sevens players - Elloumi, M.; Makni, E.; Moalla, W.; Bouaziz, T.; Tabka, Z.; Lac, G.; Chamari, K. (Asian Journal of Sports Medicine, 2012)
Purpose: Trainers and physical fitness coaches` need a useful tool to assess training loads to avoid overtraining. However, perceived scales or questionnaires were required. Therefore, the purpose of this study was to assess whether a short 8-item questionnaire of fatigue could be a useful tool for monitoring changes in perceived training load and strain among elite rugby Sevens (7s) players during preparation for a major competition.